Polar Bear Predatory Behaviour toward Molting Barnacle Geese and Nesting Glaucous Gulls on Spitsbergen - Stempniewicz, Lech (ARCTIC, 2009)
A polar bear (Ursus maritimus) was observed stalking and chasing a flock of adult flightless barnacle geese (Branta leucopsis) in a coastal bay in Hornsund, southwest Spitsbergen. Before chasing the geese, the polar bear appeared to make use of the cover provided by a rocky pier in order to swim close to them. Immediately after that unsuccessful attempt, the bear plundered a glaucous gull (Larus hyperboreus) nest situated on coastal rock and captured three nestlings. These observations are the first documented instances of a polar bear hunting for barnacle goose and glaucous gull and provide additional evidence of the use of terrestrial prey by polar bears during the season of minimal ice extent. Un ours polaire (Ursus maritimus) a été observé en train de traquer et de pourchasser une bande de bernaches nonnettes (Branta leucopsis) coureuses adultes dans une baie côtière de Hornsund, dans le sud-ouest de Spitsbergen. Avant d’avoir chassé les bernaches, l’ours polaire semblait s’être servi d’un quai rocailleux pour se cacher et nager près des bernaches. Immédiatement après cette tentative échouée, l’ours a pillé un nid de goélands bourgmestres (Larus hyperboreus) situé sur un rocher côtier et a capturé trois oisillons. Ces observations, les premiers exemples de bernaches nonnettes et de goélands bourgmestres pourchassés par un ours polaire, fournissent d’autres preuves selon lesquelles les ours polaires ont des proies terrestres pendant la saison de l’étendue minimale de glace.